New eclipsing binaries with mercury–manganese stars. Issue 1 (17th June 2021) - Kochukhov, O; Labadie-Bartz, J; Khalack, V; Shultz, M E
ABSTRACT: Eclipsing binary stars are rare and extremely valuable astrophysical laboratories that make possible precise determination of fundamental stellar parameters. Investigation of early-type chemically peculiar stars in eclipsing binaries provides important information for understanding the origin and evolutionary context of their anomalous surface chemistry. In this study, we discuss observations of eclipse variability in six mercury–manganese (HgMn) stars monitored by the Transiting Exoplanet Survey Satellite ( TESS ) satellite. These discoveries double the number of known eclipsing HgMn stars and yield several interesting objects requiring further study. In particular, we confirm eclipses in HD 72208, thereby establishing this object as the longest-period eclipsing HgMn star. Among five other eclipsing binaries, reported here for the first time, HD 36892 and HD 53004 stand out as eccentric systems showing heartbeat variability in addition to eclipses. The latter object has the highest eccentricity among eclipsing HgMn stars and also exhibits tidally induced oscillations. Finally, we find evidence that HD 55776 may be orbited by a white dwarf companion.